PENGALIHAN OBJEK JAMINAN FIDUSIA OLEH PEMBERI FIDUSIA TANPA SEPENGETAHUAN TERTULIS DARI KREDITUR MENURUT UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Angel Meilenia Ng; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2022)
Fiduciary guarantee is a guarantee for a tangible or intangible movable object and immovable object.In a fiduciary agreement, the object of the guarantee of ownership of the object remains in the hands ofthe debtor. However, the fact that happens is that debtors often transfer the object of their fiduciaryguarantee to a third party, which causes losses to the creditor. Therefore, this study aims to determinethe implementation of the droit de suite principle on the transfer of the fiduciary guarantee object andthe legal consequences if the fiduciary guarantee object is transferred without written notification tothe creditor. The research method used is normative legal research with descriptive researchproperties, and uses primary, secondary, and tertiary legal materials. The researcher obtained theresults that the droit de suite principle is always attached to the material rights, even though they aretransferred. This will have a logical consequence where if the object of the guarantee is transferredwithout being known to the creditor, the creditor can withdraw the object of the guarantee whoseownership has been transferred to another party other than the creditor and debtor.